Creative Technology : a local success story. - Law, Li Anne. (2008)
With the burgeoning growth of the Singapore economy and the exponential rate at which technology is advancing, local firms are increasingly adopting a global perspective. This is evident in the accelerating internationalization of the world's high-technology companies, which is driven by the universality of multimedia applications. In our research, we wish to derive a success formula for the enterprising local firm striving for globalizationl based on an in-depth analysis of a firm which has already attained such internationally renowned status, Creative Technology Ltd.